2016
DOI: 10.1016/j.ophtha.2016.08.041
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Optical Coherence Tomography Angiography Vessel Density and Severity of Visual Field Loss in Glaucoma

Abstract: Purpose To evaluate the association between vessel density measurements using optical coherence tomography angiography (OCT-A) and severity of visual field loss in primary open-angle glaucoma (POAG) Design Observational cross-sectional study Participants One hundred and fifty three eyes from 31 healthy, 48 glaucoma suspects, and 74 glaucoma participants enrolled in the Diagnostic Innovations in Glaucoma Study Methods All eyes underwent imaging using an OCT-A (Angiovue, Optovue; Fremont, CA) and a spectra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
290
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 369 publications
(341 citation statements)
references
References 40 publications
(54 reference statements)
31
290
3
7
Order By: Relevance
“…Partial correlation analyses between FAZ parameters and other structural/ functional parameters (cpRNFLT, mGCIPLT, and MS) were also assessed in the overall and subgroups of OAG eyes after controlling for age. 42 For the correlation between FAZ size and visual function, retinal sensitivity was expressed in both linear (1/L) and dB scales. In this study, the absolute value of correlation coefficient below 0.19 was regarded as very weak, 0.2 to 0.39 as weak, 0.4 to 0.59 as moderate, 0.6 to 0.79 as strong, and 0.8 to 1.0 as very strong correlation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial correlation analyses between FAZ parameters and other structural/ functional parameters (cpRNFLT, mGCIPLT, and MS) were also assessed in the overall and subgroups of OAG eyes after controlling for age. 42 For the correlation between FAZ size and visual function, retinal sensitivity was expressed in both linear (1/L) and dB scales. In this study, the absolute value of correlation coefficient below 0.19 was regarded as very weak, 0.2 to 0.39 as weak, 0.4 to 0.59 as moderate, 0.6 to 0.79 as strong, and 0.8 to 1.0 as very strong correlation.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we set the cutoff value of OCTA image quality at SSI >48, as used in many previous studies. 23,25,26,36,[39][40][41][42] Venugopal et al recently reported that SSI value had a significant effect on the repeatability of VD measurement by OCTA. 43 The mean SSI values of our cohort were relatively high, being close to 60, and there was no significant difference among groups in terms of SSI values.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, vascular density and FAZ area appear to correlate with visual function. Adeleh et al, [8] evaluated the association between vessel density and severity of visual field loss in primary open-angle glaucoma (POAG). They imaged 153 eyes, which contain 31 normal eyes, 48 glaucoma suspects, and 74 glaucoma eyes, by OCTA (Angiovue; Optovue, Fremont, CA).…”
Section: Applications Of Octamentioning
confidence: 99%
“…In time it can produce damage of the retinal nerve fiber layer (RNFL) and optic nerve, with loss of the related visual field [1,2]. A cup/disc (C/D) ratio (ratio of the cup located in the middle of the optic disc to the optic disc itself) higher than 0.4 raises the suspicion of glaucoma.…”
Section: Introductionmentioning
confidence: 99%